1999
DOI: 10.1253/jcj.63.373
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Free Radicals and the Damage Done to the Sarcoplasmic Reticulum During Reperfusion Injury Following Brief Ischemia in the Canine Heart

Abstract: Free radical generation was studied by the electron spin resonance (ESR) technique using -phenyl N tert butyl nitrone (PBN) in a brief ischemia-reperfusion model of the canine heart, and correlated with biochemical changes of the sarcoplasmic reticulum (SR). ESR spectra (aH = 0.3-0.4 mT, aN = 1.43-1.58 mT) were observed as PBN spin adducts, which peaked at levels 5-fold above the control levels at 5 min after reperfusion. The simulated coupling constants of PBN spin adducts suggested that the sample should con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
6
1
Order By: Relevance
“…32 Oxygen-and carbon-centered radical adducts of PBN have been detected in other canine ischemia-reperfusion systems. 3,7,28,[33][34][35] We did not detect a signal indicating the presence of free radicals in control muscle flaps. This result supports the hypothesis that free radicals are not produced in high concentrations in perfused canine gracilis muscle, even after flap dissection and transection of minor vascular pedicles and nerves.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…32 Oxygen-and carbon-centered radical adducts of PBN have been detected in other canine ischemia-reperfusion systems. 3,7,28,[33][34][35] We did not detect a signal indicating the presence of free radicals in control muscle flaps. This result supports the hypothesis that free radicals are not produced in high concentrations in perfused canine gracilis muscle, even after flap dissection and transection of minor vascular pedicles and nerves.…”
Section: Discussioncontrasting
confidence: 60%
“…This free radical adduct is thought to originate as a degradation product of the hydroxyl radical adduct of PBN. 7,26 Large deflections consistent with the presence of manganese ions 27,28 were detected in spectra obtained from effluent blood of ischemic and reperfused flaps from 2 dogs and in spectra from blood from a control flap (Fig 3).…”
Section: Resultsmentioning
confidence: 86%
“…Nrf2 is a key regulator of endogenous antioxidant systems (Itoh et al 1999; Johnson et al 2002; Lee et al 2003) and has been shown to play a neuroprotective role in the adult by preserving blood–brain barrier function following traumatic brain injury (Zhao et al 2007). Activation of Nrf2 by isothiocyanates in vitro was recently reported to protect from oxidative damage at the blood-CSF interface by maintaining low permeability of choroid plexus epithelial cells subjected to H 2 O 2 stress (Xiang et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…actors that affect the process of myocardial injury induced by ischemia -reperfusion include free radicals, 1 oxygen tension 2 and the ATP-sensitive K + channel. 3 Intracellular Ca 2+ overload also leads to myocardial injury in ischemia -reperfusion [4][5][6][7][8] and the sarcolemmal Na + /Ca 2+ exchanger (NCX) is thought to be a major factor in the excessive Ca 2+ influx.…”
mentioning
confidence: 99%